Implementasi Konsep Estetika M. Iqbal dalam Pemenuhan Kewajiban Bersama Bagi Suami Istri - Mutammimah, Bidayatul; Soleh, Achmad Khudori (Jurnal Penelitian, 2023)
AbstractAesthetics in the family can be created by fulfilling mutual obligations. Based on the will and ends with the pleasure of God. The purpose of writing this article is to describe the implementation of the aesthetic concept of M. Iqbal's ideas for the fulfillment of mutual obligations for husband and wife. This research method uses a qualitative descriptive approach that aims to explore M. Iqbal's aesthetic concepts and their implementation in fulfilling mutual obligations between husband and wife. There are three research results in this article, that M. Iqbal's aesthetic concept contained two principles, namely expression, and function. One of the means to create a sakinah mawaddah wa rahmah family is to fulfill the mutual obligations between husband and wife. The fulfillment of mutual obligations between husband and wife is the beginning of the creation of aesthetics in the family. The beautiful form of the family is oriented toward the expression of love, social function, and the Divine. This expression of love is actualized by actions to fulfill mutual obligations based on awareness of their position as husband and wife, as well as the functioning of the family as the initial environment that leads to Godhead, human development, and social progress.   AbstrakEstetika dalam keluarga dapat tercipta dengan cara saling memenuhi kewajiban bersama. Didasari dengan kemauan dan diakhiri dengan rida Tuhan. Tujuan penulisan artikel ini untuk menguraikan tentang implementasi konsep estetika gagasan M. Iqbal terhadap pemenuhan kewajiban bersama bagi suami istri. Metode penelitian ini menggunakan pendekatan deskriptif kualitatif yang bertujuan mendalami konsep estetika M. Iqbal dan implementasinya dalam pemenuhan kewajiban bersama antara suami istri. Ada tiga hasil penelitian dalam artikel ini, [1] dalam konsep estetika M. Iqbal terkandung dua prinsip, yakni ekspresi dan fungsi. [2] salah satu sarana untuk mewujudkan keluarga sakinah mawaddah wa rahmah adalah dengan memenuhi kewajiban bersama antara suami istri. [3] pemenuhan kewajiban bersama antara suami istri merupakan awal mula terciptanya estetika dalam keluarga. Bentuk keluarga yang indah berorientasi pada ekspresi cinta, fungsi sosial dan Ketuhanan. Ekspresi cinta tersebut diaktualisasikan dengan tindakan untuk saling memenuhi kewajiban bersama atas dasar kesadaran akan posisinya sebagai suami istri, serta memfungsikan keluarga sebagai lingkungan awal yang mengarahkan pada Ketuhanan, pembinaan manusia dan kemajuan sosial.